Functional changes in glutamate transporters and astrocyte biophysical properties in a rodent model of focal cortical dysplasia - Campbell, Susan L.; Hablitz, John J.; Olsen, Michelle L. (Frontiers in Cellular Neuroscience, 2014)
Cortical dysplasia is associated with intractable epilepsy and developmental delay in young children. Recent work with the rat freeze-induced focal cortical dysplasia (FCD) model has demonstrated that hyperexcitability in the dysplastic cortex is due in part to higher levels of extracellular glutamate. Astrocyte glutamate transporters play a pivotal role in cortical maintaining extracellular glutamate concentrations. Here we examined the function of astrocytic glutamate transporters in a FCD model in rats. Neocortical freeze lesions were made in postnatal day (PN) 1 rat pups and whole cell electrophysiological recordings and biochemical studies were performed at PN 21-28. Synaptically evoked glutamate transporter currents in astrocytes showed a near 10-fold reduction in amplitude compared to sham operated controls. Astrocyte glutamate transporter currents from lesioned animals were also significantly reduced when challenged exogenously applied glutamate. Reduced astrocytic glutamate transport clearance contributed to increased NMDA receptor-mediated current decay kinetics in lesioned animals. The electrophysiological profile of astrocytes in the lesion group was also markedly changed compared to sham operated animals. Control astrocytes demonstrate large-amplitude linear leak currents in response to voltage-steps whereas astrocytes in lesioned animals demonstrated significantly smaller voltage-activated inward and outward currents. Significant decreases in astrocyte resting membrane potential and increases in input resistance were observed in lesioned animals. However, Western blotting, immunohistochemistry and quantitative PCR demonstrated no differences in the expression of the astrocytic glutamate transporter GLT-1 in lesioned animals relative to controls. These data suggest that, in the absence of changes in protein or mRNA expression levels, functional changes in astrocytic glutamate transporters contribute to neuronal hyperexcitability in the FCD model.